Study protocol: safety and efficacy of propranolol 0.2% eye drops in newborns with a precocious stage of retinopathy of prematurity (DROP-ROP-0.2%): a multicenter, open-label, single arm, phase II trial - Luca Filippi; Giacomo Cavallaro; Elettra Berti; Letizia Padrini; Gabriella Araimo; Giulia Regiroli; Valentina Bozzetti; Chiara De Angelis; Paolo Tagliabue; Barbara Tomasini; Giuseppe Buonocore; Massimo Agosti; et al. (BMC, 2017)
Abstract Background Retinopathy of prematurity (ROP) still represents one of the leading causes of visual impairment in childhood. Systemic propranolol has proven to be effective in reducing ROP progression in preterm newborns, although safety was not sufficiently guaranteed. On the contrary, topical treatment with propranolol eye micro-drops at a concentration of 0.1% had an optimal safety profile in preterm newborns with ROP, but was not sufficiently effective in reducing the disease progression if administered at an advanced stage (during stage 2). The aim of the present protocol is to evaluate the safety and efficacy of propranolol 0.2% eye micro-drops in preterm newborns at a more precocious stage of ROP (stage 1). Methods A multicenter, open-label, phase II, clinical trial, planned according to the Simon optimal two-stage design, will be performed to analyze the safety and efficacy of propranolol 0.2% eye micro-drops in preterm newborns with stage 1 ROP. Preterm newborns with a gestational age of 23-32 weeks, with a stage 1 ROP will receive propranolol 0.2% eye micro-drops treatment until retinal vascularization has been completed, but for no longer than 90 days. Hemodynamic and respiratory parameters will be continuously monitored. Blood samplings checking metabolic, renal and liver functions, as well as electrocardiogram and echocardiogram, will be periodically performed to investigate treatment safety. Additionally, propranolol plasma levels will be measured at the steady state, on the 10th day of treatment. To assess the efficacy of topical treatment, the ROP progression from stage 1 ROP to stage 2 or 3 with plus will be evaluated by serial ophthalmologic examinations. Discussion Propranolol eye micro-drops could represent an ideal strategy in counteracting ROP, because it is definitely safer than oral administration, inexpensive and an easily affordable treatment. Establishing the optimal dosage and treatment schedule is to date a crucial issue. Trial registration ClinicalTrials.gov Identifier NCT02504944, registered on July 19, 2015, updated July 12, 2016. EudraCT Number 2014-005472-29.